Mature Cystic Teratoma In A Patient with Wolf Parkinson White Syndrome - KÄ±lÄ±Ã§, Murat; KOCA, Bülent (Iranian Journal of Pediatric Surgery, 2024)
In this study, we presented a 14-year-old patient who referred to a pediatric cardiology clinic with chest pain and tachycardia, whose electrocardiography examinations determined Wolf-Parkinson-White Syndrome, and in the anteroposterior chest radiography, a left-sided para-cardiac mass was detected. A lesion originating from the middle mediastinum and measuring 55×56 mm at its widest point was observed in the Computed Tomography scan. During surgery, the thorax was entered via a left muscle-sparing mini-thoracotomy, and the mass was excised completely. The histopathological examination result was evaluated as mature cystic teratoma. We presented this case because there has been no co-incidence between mature cystic teratoma and WPW syndrome in the literature before.